3D numerical study on laminar forced convection in V-baffled square channel - Boonloi, Amnart; Jedsadaratanachai, Withada (My University, 2013)
The article presents a mathematical study of fully developed periodic laminar flow visualization and heat transfer characteristics in an isothermal wall square-channel fitted with V-shaped baffles on one wall. The computations based on the finite volume method together with the SIMPLE algorithm have been performed. The investigation covers a range of Re based on the hydraulic diameter of the channel, Re = 100-1200. To create a pair of main streamwise vortex flows through the tested section, the V-baffles with the attack angle of 30° with the main flow direction are mounted in tandem and pointing downstream on the lower channel wall only. Effects of different baffle heights and pitches on heat transfer and pressure drop in the channel are examined and the results obtained are compared with smooth channel with no baffle. The numerical result shows that the presence of the V-baffle yields a significant heat transfer enhancement compared with the smooth channel. It is visible that the main vortex flows, a pair of streamwise twisted vortex (P-vortex) can induce impingement flows on the walls leading to a drastic increase in heat transfer rate over the channel. In addition, the increase in the baffle height leads to the rise in the heat transfer and pressure loss while that in the baffle pitch provides the opposite trend. The predicted results expose that the maximum thermal enhancement factors for the V-baffles with BR = 0.3, 0.3 and 0.4; and PR = 1, 1.5 and 2 are, respectively, about 2.44, 2.29 and 2.37 at higher Re. © 2013 Science Publication.
Keywords: Heat transfer; Laminar flow; Periodic flow; Square channel; V-Shaped baffle